2017
DOI: 10.1186/s40066-017-0125-5
|View full text |Cite
|
Sign up to set email alerts
|

Profitability and productivity of potato (Solanum tuberosum) in Baglung district, Nepal

Abstract: Background: Potato is considered as staple food in Hill regions of Nepal. It is considered as a major crop (in cropping pattern) of the majority of the households in Bobang and Tara VDC of Baglung district. The potato produced in these VDCs has good market reputation and is the major source of income. There are very few research studies which have assessed the profitability of potato of these areas. So, this study was aimed to assess the profitability and productivity of potato in Baglung district of Nepal. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 10 publications
8
60
1
2
Order By: Relevance
“…Ahmed et al (2009) also carried out a research on the same and the research revealed that seed and pesticides had positive but TSP and MP had negative significant effect on gross return of potato production in Mymensing district of Bangladesh. Bajracharya and Sapkota (2017) also found human labor, seed, FYM, cost of bullock labor and intercultural operation having significant effect on total income of potato in Baglung district of Nepal where an increase in 1% cost of human labor, seed and FYM would increase the total income of potato by 0.075%, 0.639% and 0.190%, whereas 1% increase in the cost of bullock labor and intercultural operation would decrease income by 0.015% and 0.047%, respectively.…”
Section: Profitability Of Potato Cultivationmentioning
confidence: 99%
See 4 more Smart Citations
“…Ahmed et al (2009) also carried out a research on the same and the research revealed that seed and pesticides had positive but TSP and MP had negative significant effect on gross return of potato production in Mymensing district of Bangladesh. Bajracharya and Sapkota (2017) also found human labor, seed, FYM, cost of bullock labor and intercultural operation having significant effect on total income of potato in Baglung district of Nepal where an increase in 1% cost of human labor, seed and FYM would increase the total income of potato by 0.075%, 0.639% and 0.190%, whereas 1% increase in the cost of bullock labor and intercultural operation would decrease income by 0.015% and 0.047%, respectively.…”
Section: Profitability Of Potato Cultivationmentioning
confidence: 99%
“…Scarcity of quality seed in sowing time is the major causes for higher seed cost and government intervention on fertilizer market by providing subsidy on fertilizer is the major cause for lower fertilizer cost of potato production. On the other hand Bajracharya and Sapkota (2017) found FYM constituted highest (45.32%) portion of the cost of production followed by seed and human labor in Baglung district of Nepal. …”
Section: Cost Of Cultivationmentioning
confidence: 99%
See 3 more Smart Citations